Personality Change: Longitudinal Self‒Other Agreement and Convergence with Retrospective-Reports - Oltmanns, Joshua R. (J Pers Soc Psychol, 2019)
The research literature on personality development is based mostly on self-report studies and on samples in younger adulthood. The present multi-method study examines self–other agreement on longitudinal personality change and convergence between self- and informant-reports of longitudinal and retrospective personality change in older adulthood. It provides a rare validation test of longitudinal measurements of personality change. A representative community sample of 1,630 older adults (M age = 62.5) and their informants completed self- and informant-personality assessments across three waves that were on average 6.5 years apart. Self- and informant-reports of retrospective personality change were collected at the third wave. Latent growth modeling was used to examine longitudinal personality change, longitudinal self–other agreement on personality change, and convergence of longitudinal and retrospective personality change in each five-factor model domain. Older adults in the present study reported less change than has been found in younger samples. Both self- and informant-reports indicated declines in extraversion. Results showed strong self–other agreement on longitudinal personality change in all five-factor model domains, moderate correspondence between longitudinal and retrospective-reports of change within-method (i.e., within self- or informant-report), modest self–other agreement on retrospective-reports, and little association between longitudinal and retrospective change acrossmethod (i.e., between self- and informant-reports). Findings provide validation evidence for both longitudinal and retrospective assessments of personality change, indicate that informants provide unique perspectives on personality change, and could have potentially important implications for research, assessment, and clinical settings.